Biomechanical evaluation of osteoporotic fracture: Metal fixation versus absorbable fixation in Sawbones models. Issue 7 (July 2019) - Wu, Xinbao; Wang, Ziyun; Li, Hui; Li, Yuneng; Wang, Hao; Tian, Wei
Abstract: Objective: The failure of osteoporotic fracture after internal fixation is mainly caused by the underlying bone loss and strength compromise. The aim of this study is to investigate whether absorbable internal fixation can provide adequate mechanical stability and a reduction in the incidence of failure of fixation caused by bone loss and stress shielding. Methods: A low density cancellous bone model was selected to compare the insertion of screw (screw-in), removal of screw (screw -out) and pull - out strength of absorbable screw and metal screw. The long bone model of thin cortical bone was used to create the transverse fracture model. The model was fixed with absorbable plate-screw system and metal plate-screw system respectively. The fatigue test and static bending test were compared. Moreover, the size of screw hole area was assessed. Results: The maximal screw - in and screw - out torque of the absorbable screw was significantly greater than that of the metal screw (P < 0.05), but there was no significant difference in pull-out test (P > 0.05). No visible failure occurred in fatigue test. There was no significant difference between the maximum load of static bending test (P > 0.05). The screw hole area of absorbable samples was significantly smaller than that of metal samples (P < 0.05). Conclusions: In this experimental set-up it was found that the stability of absorbable screws in osteoporotic bone was better than metal screws. The absorbable system tested can achieve good stability, and the destruction of osteoporotic bone is small, which can reduce the occurrence of bone failure. Considering that absorbable material avoids the need of second surgery (implant removal) and reduces the stress shielding effect, we believe that absorbable internal fixation can be considered for fixation treatment of osteoporotic fractures.